Colonialism, Enlightenment, Castration: Writing, Narration and Legibility in L'Etranger - Larry W. Riggs; Paula Willoquet-Maricondi (Studies in 20th & 21st Century Literature, 1992)
This analysis combines the issue of "narratability" with some psychoanalytic insights, focusing first on the key incident in Meursault's story when he involves himself in writing. Meursault inadvertently inscribes himself in a conflictual drama when he writes a letter for Raymond Sintès. The writing of the letter prefigures both Meursault's later taking up of the gun with which he will kill an Arab and his inexorable evolution toward a situation that makes him capable of narrating and being narrated. It seals him into the colonial world of language. To become capable of narrating is both to become a colonist and to be colonized. It requires a subject/object relationship within the self. Mersault's story is an "allegory" of becoming legible in two ways: as an individual in a real cultural situation and as a character in a novel. Our analysis also links another of the novel's underlying themes—fragmentation of the environment—with our examination of Meursault's movement toward narratability and condemnation. The unbearable intensity of the sun throughout the novel is a token of this fragmentation. The colonialists' tendency to experience their presence in Algeria as both a necessary "civilizing" influence and a noble self-sacrifice is legitimated and perpetuated by their refusal to adapt their costumes and ceremonies to the environment.
Keywords: narratability; psychoanalytic; Meursault; inscribes; Raymond Sintès; letter; Arab; narrating; narrator; narrated; colonial; language; colonist; colonized; subject/object relationship; subject; object; self; allegory; character; novel; fragmentation of the environment; fragmentation; environment; condemnation; sun; colonialists; colonialist; Algeria; civilizing; self-sacrifice; costumes; ceremonies